Buen vivir and the challenges to capitalist development in Latin America
1 online resource (xii, 219 pages)
Keywords: "This book critically explores the development and resistance dynamics generated by conflicting forces of social change in Latin America. In the current climate of worldwide capitalist development, Latin America is caught between left-leaning proposals for progressive policies towards a more inclusive form of development, and the re-emergence of harsh austerity measures, neoliberal reforms and right-wing populism. Divided into two parts, this book first provides a retrospective analysis of these forces of change, which are inherently tied up in politics on both an international and a domestic scale. The second part goes on to focus on forward-looking challenges, particularly as relates to the worldview and vision of alternative realities embedded in the indigenous notion of Vivir Bien - the concept of 'living well' in social solidarity and harmony with nature. This idea has radically transformed the thinking about 'development', which has traditionally revolved around the policy and institutional dynamics associated with the evolution of capitalism as a world system. The notion of Vivir Bien takes us beyond the world of development as we know it, into what might be understood as a form of 'postdevelopment'. Looking hopefully towards this future of development, this collection offers an essential analysis of the vortex of social change currently consuming Latin America and is key reading for advanced scholars and researchers in the field"--